2012
DOI: 10.1007/s00204-012-0935-y
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of tert-butylhydroquinone on paraquat-induced dopaminergic cell degeneration in C57BL/6 mice and in PC12 cells

Abstract: The present study was aimed at determining the role of paraquat (PQ) in the activation of the NF-E2-related factor 2 (Nrf2)/heme oxygenase 1 (HO-1) pathway and the possible neuroprotective effects of tert-butylhydroquinone (tBHQ) pretreatment on PQ-induced neurodegeneration in vivo and in vitro. 7 mg/kg PQ treatment of male C57BL/6 mice caused decreased spontaneous locomotor activity, decreased tyrosine hydroxylase (TH)-positive neurons, increased terminal deoxynucleotidyl transferase-mediated dUTP biotin nick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 38 publications
2
30
0
Order By: Relevance
“…In order to have an in vitro model of oxidative stress, neuronal cells after 7 days of culture in the PCL membrane system were initially subjected to H 2 O 2 treatment before the administration of didymin for the next 24 h. In spite of the high percentage of cell death, administration of didymin significantly attenuated cell death and reduced the intracellular ROS levels. As a positive control we used tBHQ since it is known as a strong inducer of phase II detoxification enzymes which have antioxidative functions [Hara et al, 2003;Li et al, 2012]. Lee et al [2001] demonstrated that the treatment with tBHQ prevented H 2 O 2 -induced apoptosis and induced many genes associated with resistance against oxidative stress in neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…In order to have an in vitro model of oxidative stress, neuronal cells after 7 days of culture in the PCL membrane system were initially subjected to H 2 O 2 treatment before the administration of didymin for the next 24 h. In spite of the high percentage of cell death, administration of didymin significantly attenuated cell death and reduced the intracellular ROS levels. As a positive control we used tBHQ since it is known as a strong inducer of phase II detoxification enzymes which have antioxidative functions [Hara et al, 2003;Li et al, 2012]. Lee et al [2001] demonstrated that the treatment with tBHQ prevented H 2 O 2 -induced apoptosis and induced many genes associated with resistance against oxidative stress in neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…ARE-driven genes are involved in production of a battery of antioxidant and phase 2 enzymes, which is a potent strategy to repress oxidative damage (Calkins et al, 2009). Among Nrf2-regulated phase 2 enzymes, heme oxygenase 1 (HO-1), the rate-limiting enzyme in catalysis of heme, has been reported to be critical for the protective effect of the Nrf2-ARE signaling pathway in neurodegenerative diseases (Satoh et al, 2006;Li et al, 2012;Alfieri et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Neurodegenerative diseases refer to cerebral or spinal disorders caused by abnormal neuronal death and are accompanied by impaired cognitive, walking, and motor abilities (2). As oxygen free radicals are known to be largely responsible for these degenerative diseases, more research and development into technologies to control oxygen free radicals are being conducted (3)(4)(5). Oxidative stress induces lipid peroxidation, injury to protein, cell membranes, and DNA, and cell aging and deformation, resulting in various neurodegenerative diseases such as stroke, Alzheimer's disease, and Parkinson's disease (6,7).…”
Section: Introductionmentioning
confidence: 99%